2019
DOI: 10.1038/s41598-019-39701-5
|View full text |Cite
|
Sign up to set email alerts
|

A neonicotinoid pesticide impairs foraging, but not learning, in free-flying bumblebees

Abstract: Neonicotinoids are widely-used pesticides implicated in the decline of bees, known to have sub-lethal effects on bees’ foraging and colony performance. One proposed mechanism for these negative effects is impairment to bees’ ability to learn floral associations. However, the effects of neonicotinoids on learning performance have largely been addressed using a single protocol, where immobilized bees learn an association based on a single sensory modality. We thus have an incomplete understanding of how these pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
74
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 86 publications
8
74
2
Order By: Relevance
“…We found that imidacloprid exposure also reduced the foraging activity of foragers within the colony, with individuals making fewer foraging trips in LD conditions. This is consistent with previous, field-based studies showing that exposure to imidacloprid under field conditions decreased the number of foraging trips carried out by foragers [42,43], and neonicotinoids reduced the quantity of sucrose and pollen collected by Bombus terrestris colonies [44]. This could in part be driven by reduced foraging motivation caused by the apparent appetite suppression that imidacloprid can cause, with 10 µg/L shown to decrease feeding by 30% in Bombus terrestris [13].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We found that imidacloprid exposure also reduced the foraging activity of foragers within the colony, with individuals making fewer foraging trips in LD conditions. This is consistent with previous, field-based studies showing that exposure to imidacloprid under field conditions decreased the number of foraging trips carried out by foragers [42,43], and neonicotinoids reduced the quantity of sucrose and pollen collected by Bombus terrestris colonies [44]. This could in part be driven by reduced foraging motivation caused by the apparent appetite suppression that imidacloprid can cause, with 10 µg/L shown to decrease feeding by 30% in Bombus terrestris [13].…”
Section: Discussionsupporting
confidence: 91%
“…time-givers or entrainment signals) such as light or social cues [48,49]. This may imply that the reduction in foraging rhythmicity observed for bumblebee colonies exposed to imidacloprid in the lab are likely to reflect deleterious consequences in the field, as is the case for reductions in foraging activity [42,43]. A disruption to the clock in foragers may further reduce their foraging efficiency as they will not be able to form the time-memories required to accurately visit different flowers [5,50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, negative nontarget effects of pesticides are apparent on pollinator populations (Frampton & Dorne, 2007), even as the behavioral consequences of sublethal insecticide exposure on bee foraging are an area of active research (Muth & Leonard, 2019). For example, negative nontarget effects of pesticides are apparent on pollinator populations (Frampton & Dorne, 2007), even as the behavioral consequences of sublethal insecticide exposure on bee foraging are an area of active research (Muth & Leonard, 2019).…”
Section: Multifarious Causes Of Insect Declinesmentioning
confidence: 99%
“…The associations that have been documented between stressors and insect responses point to causal relationships even though our knowledge of the mechanisms that underlie them are imperfect. For example, negative nontarget effects of pesticides are apparent on pollinator populations (Frampton & Dorne, 2007), even as the behavioral consequences of sublethal insecticide exposure on bee foraging are an area of active research (Muth & Leonard, 2019). As a consequence of imperfect knowledge, we cannot always say which stressors or interactions among stressors are more or less important in a given area or for any one species.…”
Section: Multifarious Causes Of Insect Declinesmentioning
confidence: 99%